Prevalence and gaps today; mental health tomorrow - Vicente, Benjamín; Saldivia, Sandra; Pihán, Rolando (Acta Bioethica, 2016)
WHO places Chile among countries with greater morbidity burden for psychiatric diseases in the world (23,2%). Major depression and alcohol consumption disorders hold the first and second place in disabilities attributed to adults. Almost a third of the population older than 15 years have suffered a psychiatric disorder during life span and 22,2% persons have had one in the last year. Anxiety disorders have more prevalence, followed by major depression and alcohol consumption disorders. Only 38,5% of those diagnosed receive some type of mental health care, by an specialist or a primary health care physician. In children and adolescent, prevalence of any psychiatric disorder is 22,5% (19,3% for boys and 25,8% for girls). These disorders are mainly disruptive and of anxiety. Prevalence is higher for children between 4 to 11 years (27,8%) than between 12 and 18 years, and this difference is due mainly to disruptive disorders. Prevalence of anxiety disorders is the second highest, even though less associated with disabilities, while many children and adolescents with affective disorders are disabled and only a fifth of persons with health care needs look for some form of care. Almost a fourth of those that use health care services did not present psychiatric diagnosis during last year. Co morbidity occurs in 27% of those with disorders, but only 7% have three or more diagnosis. Not addressing treatment gap in mental health has serious implications in public health.